cis-Acting Elements Responsible for Low-Temperature-Inducible Expression of the Gene Coding for the Thermolabile Isocitrate Dehydrogenase Isozyme of a Psychrophilic Bacterium, Vibrio sp. Strain ABE-1 - Sahara, Takehiko (American Society for Microbiology, 1999)
Transcriptional control of the low-temperature-inducible icdII gene, encoding the thermolabile isocitrate dehydrogenase of a psychrophilic bacterium, Vibrio sp. strain ABE-1, was found to be mediated in part by a transcriptional silencer locating at nucleotide positions −560 to −526 upstream from the transcription start site of icdII. Deletion of the silencer resulted in a 20-fold-increased level of expression of the gene at low temperature (15°C) but not at high temperature (37°C). In addition, a CCAAT sequence located 2 bases upstream of the −35 region was found to be essential for the low-temperature-inducible expression of the gene. By deletion of this sequence, low-temperature-dependent expression of the gene was completely abolished. The ability of the icdII promoter to control the expression of other genes was confirmed by using a fusion gene containing the icdII promoter region and the promoterless icdI open reading frame, which encodes the non-cold-inducible isocitrate dehydrogenase isozyme of Vibrio sp. strain ABE-1. Escherichia coli transformants harboring icdII acquired an ability to grow rapidly at low temperature.